Accelerating Poverty Reduction in a Less Poor World : The Roles of Growth and Inequality - Olinto, Pedro; Lara Ibarra, Gabriel; Saavedra-Chanduvi, Jaime (World Bank, Washington, DC, 2014)
This paper re-examines the roles of changes in income and inequality in poverty reduction. The study provides estimates of the relative effects of inequality reduction versus growth promotion in reducing poverty for countries with different levels of initial poverty. The analysis uses country panel-data for 1980-2010. The results indicate that, as countries become less poor, inequality-reducing policies are likely to become relatively more effective for poverty reduction than growth-promoting policies. The results indicate that the growth elasticity of poverty reduction either increases or remains constant with the level of initial poverty. Nevertheless, the results also strongly indicate that, as poverty declines, the inequality elasticity of poverty reduction increases faster. Therefore, if the marginal cost of reducing inequality relative to the marginal cost of increasing growth does not increase with lower poverty levels, to accelerate poverty reduction, greater emphasis should be given to equity rather than growth as countries attain higher levels of development.